09/11 on the USD/EUR Foreign Exchange Market - Alexander Mende (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2005)
We study the relationship between foreign exchange trading activity and volatility on the USD/EUR foreign exchange market on the basis of a unique data set around the events of 09/11/2001. We find that volatility and bid-ask spreads are by far larger at that time, but the shock is not persistent. The positive correlation between volume and volatility does not break up, but intensifies strongly indicating the arrival of new information and increased price risk. We conclude that the USD/EUR foreign exchange market maintains its liquid structure and its efficient processing of exogenous shocks.
Keywords: G14; F31; G15; 330; foreign exchange; market microstructure; liquidity; sudden events